MAGIC library – A tool to assess surface water acidification. (May 2020) - Moldan, Filip; Stadmark, Johanna; Jutterström, Sara; Kronnäs, Veronika; Blomgren, Håkan; Cosby, Bernard J.
Highlights: MAGIC library provides an acidification assessment for any lake or stream in Sweden. The assessment is based on analogue matching technique and a library of model runs. The matching is based on position, lake size, discharge and water chemistry. In >90% of the cases the library is consistent with a site-specific MAGIC run. Abstract: We have developed a tool, the MAGIC library, which provides an acidification assessment for any given lake or stream in Sweden based on ten parameters describing lake geographical position, surface area, annual discharge and observed lake water chemistry. The MAGIC library consists of two key components: a library of the existing MAGIC model simulations for 2438 lakes and an analogue matching routine that selects the library lake which is most similar to the evaluation lake described by the ten parameters. The acidification assessment modelled by MAGIC for the library lake is then assumed valid for the evaluation lake. For more than 90% of the library lakes tested, the MAGIC library provided the same acidification assessment as the site-specific MAGIC model simulation. Labour and data requirements for assessment by the MAGIC library are very modest relative to the needs of site-specific MAGIC (or other similar) model simulations. The relative ease of use is essential for a country like Sweden, with a population of 100 000 lakes. The MAGIC library has a web interface (http://magicbiblioteket.ivl.se ) to provide single assessments interactively or multiple assessments by uploading the ten required parameters for multiple sites. Conceptually the library has built-in flexibility and could be adapted for other types of ecosystems or assessments. In this paper we describe the MAGIC library concept and evaluate the performance of the MAGIC library in comparison to site-specific MAGIC modelling.